PELATIHAN MEMBANGUN SDM KREATIF BERKELANJUTAN KELOMPOK PEMBERDAYAAN MASYARAKAT “BUMI RESIK MARUGA” - Rodhiah; Putri, Nadira Aulia; Clarisa, Tara (Transpublika Publisher, 2023)
Business competition in the creative industry requires the right competitive strategy. The strategy necessitates focusing on product quality with high market demand, competitive pricing, a robust supply chain, and appropriate allocation of funds. All of these factors are influenced by the application of competent human resources (HR). The purpose of this activity is to help business owners gain the knowledge necessary to build sustainable and creative HR practices. The activity took place at the Bumi Resik Maruga community empowerment group located in South Tangerang. The selected partner is a recycling business group that transforms large and small used plastic bottles into handicraft products such as lampshades, aquariums, flower pots, and more. Based on initial observations made by directly engaging with the partners, the main problem lies in managing creative human resources due to the partners' weak knowledge about HR management. As a result, they have not been able to leverage their competitive advantage effectively. To address this issue, the method offered in the activity is training and socialization. The results of the activity show that it was successful, with partners enthusiastically embracing the material presented by the PKM Team. Through this initiative, the problems encountered in the recycling business can be resolved, and partners can enhance their knowledge in building and maintaining creative human resources to compete effectively in producing sustainable and creative products.